2002
DOI: 10.1124/jpet.301.2.594
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Metabolism of Nicotine and Cotinine in Pregnant Smokers

Abstract: Cigarette smoking is the foremost modifiable risk factor for adverse pregnancy outcomes. Nicotine is a suspected fetal neuroteratogen. There is concern that nicotine may achieve toxic levels during pregnancy if nicotine replacement therapies are prescribed at doses used in the nonpregnant state. Ten healthy, volunteer, pregnant smokers received infusions of deuterium-labeled nicotine and cotinine during pregnancy and again postpartum. From blood and urine measurements, the following were determined: clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
312
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 406 publications
(330 citation statements)
references
References 39 publications
14
312
1
3
Order By: Relevance
“…Nicotine/cotinine ratios in the third trimester were significantly decreased compared to those in the first trimester. According to the authors, these findings illustrated that nicotine metabolism to cotinine, mainly catalyzed by CYP2A6, increases as pregnancy advances [56], which was in agreement with previous findings [57]. In a more recent study by the same group, similar results for nicotine/cotinine ratios in hair of 74 smoking women were obtained [58].…”
Section: Hairsupporting
confidence: 86%
“…Nicotine/cotinine ratios in the third trimester were significantly decreased compared to those in the first trimester. According to the authors, these findings illustrated that nicotine metabolism to cotinine, mainly catalyzed by CYP2A6, increases as pregnancy advances [56], which was in agreement with previous findings [57]. In a more recent study by the same group, similar results for nicotine/cotinine ratios in hair of 74 smoking women were obtained [58].…”
Section: Hairsupporting
confidence: 86%
“…The oxidation kinetics for nicotine and cotinine are considered to be different (Hukkanen et al, 2005;Benowitz et al, 2009), and conversion of cotinine to 3HC is likely more sensitive than altered clearance of nicotine to changes in CYP 2A6 activity. Dempsey et al, 2002 found that cotinine levels were lower in pregnancy despite similar nicotine (smoking) exposure, and that although nicotine clearance increased by 60% (54% via the cotinine pathway), cotinine clearance increased by 140%. This change was attributed to increased activity of CYP 2A6, which had greater effects on the clearance of cotinine than of nicotine.…”
Section: Rapid Nicotine Clearance Associated With Greater Reward M Somentioning
confidence: 99%
“…In a large nonrandomised clinical sample (3500 participants), transdermal NRT combined with an oral form doubled the quit rate compared with no medication or monotherapy (OR = 1.93) (Brose et al 2013). The accelerated nicotine metabolism in pregnancy gives a physiological basis for higher doses being required (Dempsey et al 2002). Even short periods of abstinence are beneficial for foetal growth.…”
Section: Dangers Of Quitting and Treatmentmentioning
confidence: 99%